1975
DOI: 10.1111/j.1365-246x.1975.tb01610.x
|View full text |Cite
|
Sign up to set email alerts
|

Seismology, dT/d  and Deep Mantle Convection

Abstract: dT/dA and azimuth measurements at the Yellowknife Seismic Array (YKA) for P and pP phases that have penetrated to depths greater than 1850 km show systematic bias relative to those values calculated from spherically symmetric Earth models. Moreover, the corresponding arrival vectors for the phases PcP, ScP, PnKP and SnKP (n > 2) approaching YKA from within the same narrow azimuth ranges as the P andpP phases show related systematic errors. From an analysis of combinations of all these phases, we show that most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Such a model would provide a heat sink required to maintain an appropriate temperature gradient in the outer core. The present seismic evidence suggests that partial melting, if it occurs, can only be highly localized; for example short-period body waves which pass the deep mantle as an S wave have been widely observed (Wright & Lyons 1975).…”
Section: Scale Lengths Of Inhomogeneitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Such a model would provide a heat sink required to maintain an appropriate temperature gradient in the outer core. The present seismic evidence suggests that partial melting, if it occurs, can only be highly localized; for example short-period body waves which pass the deep mantle as an S wave have been widely observed (Wright & Lyons 1975).…”
Section: Scale Lengths Of Inhomogeneitiesmentioning
confidence: 97%
“…Lateral heterogeneity in the lower mantle has been suggested on the basis of a variety of body wave studies. Anomalies were inferred from diffracted P wave patterns (Phinney & Alexander 1966), travel times (Julian & Sengupta 1973;Jordan & Lynn 1974), ray parameters (Johnson 1969;Husebye, Kanestrom & Rud 1971), slowness vectors (Davies & Sheppard 1972;Kanasewich et al 1973;Wright & Lyons 1975) and amplitudes (Needham & Davies 1973). Despite the accumulated evidence a consistent picture has not yet emerged; Okal & Kuster (1975) discussed some of the inconsistencies.…”
Section: Introductionmentioning
confidence: 99%
“…The velocity increases at the top of D 00 are primarily detected by reflections and triplications, which arrive ahead of the corereflected PcP and ScS phases (e.g., Avants et al, 2006b;Chaloner et al, 2009;Ding and Helmberger, 1997;Gaherty and Lay, 1992;Houard and Nataf, 1993;Hutko et al, 2008Hutko et al, , 2009Kendall and Nangini, 1996;Kendall and Shearer, 1994;Kito and Krü ger, 2001;Kito et al, 2004Kito et al, , 2007aKohler et al, 1997;Lay and Helmberger, 1983a;Lay et al, 2004aLay et al, , 2006Reasoner and Revenaugh, 1999;Sun and Helmberger, 2008;Sun et al, 2006Sun et al, , 2009Takeuchi and Obara, 2010;Thomas and Weber, 1997;Thomas et al, , 2004aThorne et al, 2007;Weber, 1993;Weber and Davis, 1990;Wright and Lyons, 1975;Wright et al, 1985;Lay, 1987a, 1990). The clearest observations of deep mantle triplications are from distances of 65 to 95 , where the critical angle interaction with the velocity increase greatly enhances the amplitudes of the reflected signals relative to precritical distance ranges.…”
Section: Seismic Wave Triplicationsmentioning
confidence: 99%
“…(1975). Other studies have indicated the presence of very large-scale seismic velocity anomalies throughout the mantle, the largest amplitude anomalies being in the upper mantle and near the core-mantle boundary (Niazi 1973;Julian & Sengupta 1973;Wright & Lyons 1975;Dziewonski, Hager & O'Connell 1977). These largescale anomalies correlate with long-wavelength components of the gravity field (Dziewonski et al 1977), which suggests that they are directly associated with motion of the mantle (O'Connell 1977).…”
Section: S E I S M O L O G I C a L E V I D E N C Ementioning
confidence: 99%